66-1x=66

Simple and best practice solution for 66-1x=66 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 66-1x=66 equation:



66-1x=66
We move all terms to the left:
66-1x-(66)=0
We add all the numbers together, and all the variables
-x=0
x=0/-1
x=0

See similar equations:

| x1=−6;x2=−12 | | 17u+38=2u+53 | | 3x-5=80 | | 16x+3=195 | | x^2-20x+8=-6 | | 2t-78=t | | 16=6z-44 | | -2=p-7/4 | | 19x+3=195 | | 5x-(x-2)=14 | | 11x/30=6 | | 2p+47=15p+34 | | 2y+38=180 | | 2p+47=15p | | 5x=18+4x | | 18-(x-4)=9 | | –15q+20=–18+4q | | Y=(12+2x)+(15+2x) | | 13-10x=253 | | 7x+60=3x+68 | | 7x+60=3x+6822 | | -9=m/5-12 | | 6v-75=v | | 2a=10+8-4 | | −3/1​=4/j​−3/10​ | | 0.2x+3.5=-1.7 | | 7.05=12+2x | | 4(x–6)=44 | | 4×+3y=12 | | 0.2x+3.5=1.7 | | 6x+8=16x+8 | | (11x+7)+(5x-3)=180 |

Equations solver categories